Anaerobic Capacityestimated in A Single Supramaximal Test in Cycling: Validity and Reliability Analysis - Miyagi, Willian Eiji [UNESP]; De Poli, Rodrigo De Araujo Bonetti [UNESP]; Papoti, Marcelo; Bertuzzi, Romulo; Zagatto, Alessandro Moura [UNESP] (Springer Nature, 2017)
The aim was to verify the validity (i.e., study A) and reliability (i.e., study B) of the alternative maximal accumulated oxygen deficit determined using onlya supramaximal effort (MAODALT)to estimate anaerobic capacity [i.e., estimated by the gold standard maximal accumulated oxygen deficit method (MAOD)] during cycling. In study A, the effects of supramaximal intensities on MAODALT and the comparison with the MAOD were investigated in fourteen active subjects (26 ± 6 years). In study B, the test-retest reliability was investigated, where fourteen male amateur cyclists (29 ± 5 years) performed the MAODALT twice at 115% of the intensity associated to maximal oxygen uptake (iVO2max). MAODALT determined at 130 and 150% of iVO2max was lower than MAOD (p ≤ 0.048), but no differences between MAODALT determined at 100, 105, 110, 115, 120 and 140% of iVO2max (3.58 ± 0.53L; 3.58 ± 0.59L; 3.53 ± 0.52L; 3.48 ± 0.72L; 3.52 ± 0.61L and 3.46 ± 0.69L, respectively) with MAOD (3.99 ± 0.64L). The MAODALT determined from the intensities between 110 and 120% of iVO2max presented the better agreement and concordance with MAOD. In the test-retest, the MAODALT was not different (p > 0.05), showed high reproducibility when expressed in absolute values (ICC = 0.96, p < 0.01), and a good level of agreement in the Bland-Altman plot analysis (mean differences ± CI95%:-0.16 ± 0.53L). Thus, the MAODALT seems to be valid and reliable to assess anaerobic capacity in cycling.